Imaging blood-brain barrier dysfunction: A state-of-the-art review from a clinical perspective - Moyaert, Paulien; Padrela, Beatriz E.; Morgan, Catherine A.; Petr, Jan; Versijpt, Jan; Barkhof, Frederik; Jurkiewicz, Michael T.; Shao, Xingfeng; Oyeniran, Olujide; Manson, Tabitha; Wang, Danny J. J.; Günther, Matthias; et al. (Frontiers in Aging Neuroscience, 2023)
Background: The blood-brain barrier (BBB) consists of specialized cells that tightly regulate the in- and outflow of molecules from the blood to the brain parenchyma, protecting the brain’s microenvironment. If one of the BBB components starts to fail, its dysfunction can lead to a cascade of neuroinflammatory events leading to neuronal dysfunction and degeneration. Main body: Preliminary imaging findings suggest that BBB dysfunction could serve as an early diagnostic and prognostic biomarker for a number of neurological diseases. This review aims to provide clinicians with an overview of the emerging field of BBB imaging in humans by answering three key questions: (1. Disease) In which diseases could BBB imaging be useful? (2. Device) What are currently available imaging methods for evaluating BBB integrity? And (3. Distribution) what is the potential of BBB imaging across all settings, particularly in resource-limited settings? Conclusion: BBB imaging holds the potential to enable earlier diagnosis and aid in the recruitment of individuals and rapid assessment of treatment response in clinical trials. Further advances are needed, such as the validation, standardization, and implementation of readily available, low-cost, and non-contrast BBB imaging techniques, for BBB imaging to be a useful clinical biomarker in both resource-limited and well-resourced settings.